Entrepreneurial Leadership and Business Performance in MSMEs in the Digital Era: A Systematic Literature Review - Duki Adam; Ade Banani; Ratno Purnomo (Fundamental and Applied Management Journal, 2026)
Over the past decade, research on entrepreneurial leadership in MSMEs has grown both in terms of quantity and thematic depth, shifting from conceptual analyses toward empirical studies. The purpose of this study is to summarize the literature, identify key empirical gaps, and formulate research recommendations and practical implications for MSME practitioners and policymakers. This study employs a systematic literature review using the PRISMA methodology on 21 articles from the Scopus database spanning the period from 2016 to 2025. The findings indicate that entrepreneurial leadership has been proven to enhance employee creativity, innovative work behavior, and organizational innovation capabilities. These findings underscore the importance of investing in the development of entrepreneurial leadership competencies, fostering a culture of learning and ethics, and implementing managerial practices that support innovation and technology adoption to accelerate knowledge transfer and enhance the competitiveness of MSMEs. A limitation of this study is that it only used the Scopus database with open-access articles in English, only included articles with at least 21 citations, only considered articles containing the keywords “entrepreneurial leadership” and “SMEs,” and relied solely on the Scopus database. Future research could expand the database, language options, and include non-open-access articles